Financial Technology on Banking Financial Performance with Audit Quality as Moderating Variable - Butar-Butar, Dea Tiara Monalisa; Serly, Serly; Ramadana, Mariska (Fakultas Teknik dan Ilmu Komputer, Universitas Sains Al-Qur'an (UNSIQ) Wonosobo, 2024)
The purpose of this study is to determine the effect of fintech on banking financial performances as seen from profitability and liquidity risk with audit quality as moderating variable. The urgency of this research is due to the inconsistency of results in testing the effect of fintech on banking financial performance. In addition, this study also considers the audit quality variable as moderating variable to see whether the audit quality can stengthen or weaken the effect of fintech on banking financial performance. This research is descriptive research with quantitative approach. The population used in this study were all banking companies listed on the IDX for the 2020-2022 period. The study’s samples, which were chosen using the purposive sampling technique, include banks that periodically released yearly financial reports throughout the research period and have used fintech services such phone, SMS, and internet banking. Managing data using Eviews 12. The findings demonstrated that financial technology significantly affects LDR and ROA. However, as a moderating variable, the audit quality variable has no discernible effect on ROA or LDR.